Toward A Comprehensive Interpretation Of Ritual - Clothey, Fred W. (Journal of ritual studies, 1988)
This essay represents a groping for a comprehensive hermeneutics of religious phenomena by highlighting some of the concerns that have become part of my method for interpreting rituals in contemporary South Indian contexts. These concerns are not unrelated to the hermeneutical process more broadly conceived, for the method spelled out here is derived selectively from a variety of approaches; especially those that are phenomenological, anthropological, historical, and morphological.